2020
DOI: 10.5603/arm.a2020.0193
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Fixed Time and Self-Paced Walking Tests in Patients Diagnosed with Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is a specific form of chronic fibrosing interstitial pneumonia that has an unknown etiology. The natural history of the disease is characterized by a progressive decline in pulmonary function and overall health and well-being. The median survival time is between 2-3 years; however, the disease course is variable and unpredictable. The twelve-minute walking test (12MWT) and six-minute walking test (6MWT) are two fixed time tests that are commonly used in clinical practice. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Similar to the previous findings, significant weight loss was associated with poor outcomes in our study. It was associated with a poor prognosis even after adjusting for well-known prognostic factors such as 6MWD, baseline albumin levels, and lung function 1 , 30 , 31 . Therefore, it can be suggested that careful monitoring of weight loss is necessary when treating patients with IPF.…”
Section: Discussionmentioning
confidence: 97%
“…Similar to the previous findings, significant weight loss was associated with poor outcomes in our study. It was associated with a poor prognosis even after adjusting for well-known prognostic factors such as 6MWD, baseline albumin levels, and lung function 1 , 30 , 31 . Therefore, it can be suggested that careful monitoring of weight loss is necessary when treating patients with IPF.…”
Section: Discussionmentioning
confidence: 97%